2012
DOI: 10.4103/2230-8229.98290
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and attitude of health professionals in the Riyadh region, Saudi Arabia, toward complementary and alternative medicine

Abstract: Background:Complementary and alternative medicine (CAM) is a popular treatment option for many populations. The present work is aimed at studying the knowledge and attitude of health professionals in the Riyadh region, Saudi Arabia, toward CAM.Material and Methods:In this cross-sectional survey, a multistage random sample was taken from health professionals working in hospitals in Riyadh city and surrounding governorates. Data were collected through a self-administered questionnaire, from 306 health profession… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 28 publications
3
18
0
Order By: Relevance
“…Accordingly, medical students reported that their most important sources of CAM information were peers, scientific journals, media, and Internet, and these results are partially consistent with other reports. 30 Predictably, this CAM info-source scenario would change in future when CAM course will be integrated into main curriculum of all medical schools in KSA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, medical students reported that their most important sources of CAM information were peers, scientific journals, media, and Internet, and these results are partially consistent with other reports. 30 Predictably, this CAM info-source scenario would change in future when CAM course will be integrated into main curriculum of all medical schools in KSA.…”
Section: Discussionmentioning
confidence: 99%
“…A PubMed search of relevant literature using key word complementary and alternative medicine retrieved a dozen of articles; 27 39 however, only few studies assessed the KAP of public, professionals, primary care physicians, and pharmacists. 27 , 30 32 , 36 The results of these studies suggest that CAM therapies, especially herb preparations and locally known therapies are used by a substantial number of patients, and public and professionals have positive attitudes toward CAM, identified some barriers against CAM, and have good knowledge in CAM, and further express to have more knowledge in CAM and support its integration into primary health care 27 , 30 32 , 36 and medical schools. 39 We found only one study from Kuwait that assessed KAP of CAM therapies among medical and pharmacy students.…”
Section: Introductionmentioning
confidence: 99%
“…Interest in traditional and complementary medicine (T&CM) has grown considerably in recent years not only among the public, but also among medical professions, decision makers, and researchers in Saudi Arabia. 1 , 2 , 3 , 4 In the absence of a national survey, multiple regional surveys showed that TM use is ranging from 60 to 75%. 5 , 6 , 7 Religious healings, herbal medicine, cupping therapy, and the healing with honey are the leading four therapies respectively in TM in Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%
“… 5 , 6 , 7 Religious healings, herbal medicine, cupping therapy, and the healing with honey are the leading four therapies respectively in TM in Saudi Arabia. 1 , 6 There is no Traditional Healing System similar to China, Korea, Japan, or India. However, the term “Traditional Arabic and Islamic Medicine” (TAIM) is used in Saudi Arabia like other regional and Arab countries to refer to a group of healing therapies practiced in the Arab and Islamic world within the context of religious influences of Islam.…”
Section: Introductionmentioning
confidence: 99%
“…During the last decade, the use of complementary medicine has increased in both developing and developed countries [2]. Globalization has led to intercultural exchanges and widespread use of techniques and therapeutic T&CM products often unknown to local communities [3]. …”
Section: Introductionmentioning
confidence: 99%